Divorce due to Polygamy from the Collection of Islamic Judgments (Analytical Jurisprudence Study) | قضية الطلاق بسبب تعدد الزوجات (دراسة فقهية تحليلية على قرارات المحكمة الشرعية باليمبانج سنة 2017-2016) من جمع الأحكام الإسلامية - Zuhrotul Aini Mansur; Nur Fitri Ana (Al-Zahra : Journal for Islamic and Arabic Studies, 2019)
The Islamic Judgment Collection in Chapter 113 stipulated that the interruption of marriage occurs due to death, divorce, and the court’s decision. Divorce is one of the reasons for the breakdown of the marital bond considered in Islamic jurisprudence and also considered in the collection of Islamic rulings. And polygamy was one of the reasons leading to divorce. This research aims to analyze divorce due to polygamy in the Shaimbang Court in 2016-2017.The approach used by the researcher in this research is the descriptive approach, which is describing the opinions of jurists on divorce and polygamy. The inductive and analytical method, by collecting the documents issued by the Shaimpang Sharia Court on the occurrence of divorce due to polygamy in that city, and analyzing it by reviewing the field in the Shapang Shariah Court and the personal interview with the Shapang Sharia Court Judge.Among the most important results obtained by the researcher in this research, is that the divorce due to polygamy in the Sharia Court in Lembang in 2016-2017 is small. Divorce due to polygamy in the Lembang Sharia Court occurs on three reasons: the first: negligence in giving the right to alimony to his wives and children, and the second: unfairness in polygamy, and the third: lack of responsibility for the husband.